2002
DOI: 10.1016/s0960-9822(02)00929-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Signaling Is Required for a Critical Early Step in Zebrafish Pancreatic Development

Abstract: The mechanisms that subdivide the endoderm into the discrete primordia that give rise to organs such as the pancreas and liver are not well understood. However, it is known that retinoic acid (RA) signaling is critical for regionalization of the vertebrate embryo: when RA signaling is either prevented or augmented, anteroposterior (AP) patterning of the CNS and mesoderm is altered and major developmental defects occur. We have investigated the role of RA signaling in regionalization of the zebrafish endoderm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
303
3
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(336 citation statements)
references
References 33 publications
26
303
3
4
Order By: Relevance
“…Because we used a relatively high concentration (20%) of serum during EB formation (three-dimensional differentiation), the optimal range of serum concentrations for endodermal differentiation seems to vary depending on the culture conditions. RA generated from lateral plate mesoderm has recently been reported to control Pdx1 expression in early pancreatic development in mice and zebrafish [36][37][38]. Our study demonstrated that RA treatment at the end of EB formation efficiently upregulated PDX1 expression, together with FOXA2 and SOX17 expression, while strongly downregulating the expression of MIXL1 and T, both of which were previously used as markers of the mesendodermal differentiation of ESCs [35].…”
Section: Discussionsupporting
confidence: 59%
“…Because we used a relatively high concentration (20%) of serum during EB formation (three-dimensional differentiation), the optimal range of serum concentrations for endodermal differentiation seems to vary depending on the culture conditions. RA generated from lateral plate mesoderm has recently been reported to control Pdx1 expression in early pancreatic development in mice and zebrafish [36][37][38]. Our study demonstrated that RA treatment at the end of EB formation efficiently upregulated PDX1 expression, together with FOXA2 and SOX17 expression, while strongly downregulating the expression of MIXL1 and T, both of which were previously used as markers of the mesendodermal differentiation of ESCs [35].…”
Section: Discussionsupporting
confidence: 59%
“…While inhibition of RA signaling in the late stages has little effect on the expression of anterior mesodermal markers, it abrogates pancreatic marker expression. In addition, zebrafish and Xenopus embryos treated with exogenous RA showed enlargement of the pancreas, as well as enlargement of the liver in zebrafish, in the anterior direction (Stafford and Prince, 2002;Chen et al, 2004;Stafford et al, 2004). A recent study reported that RA is sufficient to induce pancreas-specific gene expression in the dorsal but not the ventral endoderm (Pan et al, 2007).…”
Section: In Vitro Pancreas-induction Systems Using Undifferentiated Xmentioning
confidence: 96%
“…During embryonic development, the pancreatic primordium is derived from definitive endoderm that subsequently gives rise to the primitive gut and posterior foregut. At this stage, formation of the pancreatic anlage is guided by retinoid signaling and depends on inhibition of hedgehog signaling (Lau et al 2006;Stafford and Prince 2002;Stafford et al 2004). The developing pancreas is consists of epithelial progenitors expressing: Pdx1 (Ipf1), Hnf6 (Onecut), Hlxb9, Ptf1a and Nkx6-1 that will give rise to endocrine, exocrine and ductal cells (Gu et al 2002;Wilson et al 2003).…”
Section: Pancreas Developmentmentioning
confidence: 99%